Da zdravstvuyet SSSR – sotsialisticheskoye gosudarstvo rabochikh i krest'yan! - Kokorekin, Alexei Alexeyevich (Изобразительное искусство, 1938)
Worker and peasant shaking hands and holding flag of the Soviet Union Original title: Да здравствует СССР – социалистическое государство рабочих и крестьян! Suggested translation: Long live the USSR - the socialist state of workers and peasants! PO-0075